Antibiotic resistance in Bartonella bacilliformis clinical isolates from an endemic area of Peru - Silva-Caso, W. (2015)
Bartonella bacilliformis is a facultative, intracellular, aerobic, Gram-negative coccobacillus causing the so-called Carrión's disease, a human infection endemic to specific areas mainly inhabited by low-income communities of Peru but also present in other Andean communities. It is considered a truly neglected tropical disease and is transmitted through the bite of female sandflies of the genus Lutzomyia.